AB0815 Fracture Risk in A Sample of Tunisian Women Using FRAX Tool. (10th June 2014) - Sahli, H.; Slouma, M.; Rekik, S.; Elleuch, M.; Haj SAlah, A.; Zouari, B.; Cheour, E.
Abstract : Background: This is the second part of the study about the prevalence of osteoporotic fractures in the Tunisian population and which includes 1311 women, aged 64.07±9.31 years, which revealed the presence of fractures in 212 women (16.2%), mainly represented by vertebral fractures (59.83%). What about the subsequent risk of fracture in this cohort? [1] Objectives: The aim of this study was to determine the probability of fracture predicted by Frax (fracture risk assessment tool) comparing women with and without history of fracture. Methods: A prospective and comparative cohort of 111 postmenopausal women with medical history of fracture (G1) and 111 postmenopausal women without medical history of fracture (G2), matched for age, race and body mass index were included in the study. BMD was measured by dual energy X-ray absorptiometry (DXA) at lumbar spine and femoral neck. We calculated Frax values for hip in both groups and evaluated osteoporotic fracture in this cohort. Both statistical and descriptive analyses were performed. Results: The mean age was 65.92±9.48 years in G1 and 64.55±9.98 years in G2 (p=0.296). BMI values in G1 and G2 were respectively 29.18±4.96 and 28.82±4.62 kg/m 2 (0.573). Mean values of FRAX TOOL for major osteoporotic fracture in G1 and G2 were respectively 1.507±0.788 and 0.764±0.390 (p=0.000). And, mean Frax values for hip fracture in G1 and G2 were 0.384±0.504 and 0.161±0.232 respectively (p=0.000). The discriminative capacity of FRAX analyzed by the Area Under Curve (AUC), Receiver Operating Characteristics (ROC). The AUC were 0.873 (CI 95%; 0.827-0.919) for major osteoporotic fracture and 0.68 (CI 95%; 0.612-0.752) for hip fracture. Therefore odds ratio for major osteoporotic and hip fracture were 18.2 and 3.1. Conclusions: Our study confirmed the significant increase of fracture risk in patients with a history of fracture thereby enhancing the need to strengthen prevention of osteoporosis fracture in our population. Furthermore, our study demonstrated that in Tunisian female patients, cut-off FRAX values are 0.873 and 0.68 for major osteoporotic fracture and hip fracture respectively References: Sahli H, Testouri N, Chihaoui MB, Salah AH, Cheour E, Meddeb N, Zouari B, Sellami S. Bone mineral density in healthy Tunisian women. Maturitas. 2009 Jul 20;63(3):227-32 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5697